Changes in characteristics of inpatient respiratory conditions from 2019 to 2021 (before and during the COVID-19 pandemic) - Zahra Mojtahedi; Ji Yoo; Pearl Kim; Yonsu Kim; Jay J. Shen; Bing-Long Wang (Frontiers Media S.A., 2023)
BackgroundThe COVID-19 pandemic has resulted in an increase in the number of individuals with respiratory conditions that require hospitalization, posing new challenges for the healthcare system. Recent respiratory condition studies have been focused on the COVID-19 period, with no comparison of respiratory conditions before and during the pandemic. This study aimed to examine hospital-setting respiratory conditions regarding potential changes in length of stay (LOS), mortality, and total charge, as well as socioeconomic disparities before and during the pandemic.MethodsThe study employed a pooled cross-sectional design based on the State Inpatient Data Nevada for 2019 (prior to the COVID-19 pandemic) and 2020-2021 (during the pandemic) and investigated all respiratory conditions, identified by the International Classification of Disease, 10th Revision codes (n = 227,338). Descriptive analyses were carried out for the three years. Generalized linear regression models were used for multivariable analyses. Outcome measures were hospital LOS, mortality, and total charges.ResultsA total of 227,338 hospitalizations with a respiratory condition were included. Hospitalizations with a respiratory condition increased from 65,896 in 2019 to 80,423 in 2020 and 81,018 in 2021. The average LOS also increased from 7.9 days in 2019 to 8.8 days in 2020 but decreased to 8.1 days in 2021; hospital mortality among patients with respiratory conditions increased from 7.7% in 2019 to 10.2% but decreased to 9.6% in 2021; and the total charges per discharge were $159,119, $162,151, and $161,733 from 2019 to 2021, respectively (after adjustment for the inflation rate). Hispanic, Asian, and other race patients with respiratory conditions were 1-3 times more likely than white patients to have higher mortality and LOS. Medicaid patients and non-White patients were predictors of a higher respiratory-related hospital total charge.ConclusionDemographic and socioeconomic factors were significantly associated with respiratory-related hospital utilization in terms of LOS, mortality, and total charge.